Energy Storage Technologies and Applications - Faheem Zobaa, Ahmed (IntechOpen, 2013)
Besides new methods of generating energy, the storage of that energy is a highly important topic, with new technologies in great demand. This book offers readers a range of potential options, maximizing the possibility for success. Several chapters offer overviews of the future of such systems and estimations of their feasibility. Forms of energy storage covered include electrochemical, compressed air and flywheel systems. Other techniques addressed are the use of single- and double-switch cell voltage equalizers and hybrid energy storage and applications. Dynamic energy storage methods are also covered by two chapters. Finally, there are contributions on a low-voltage DC system with storage and distributed generation interfaced systems, and the in-situ dynamic characterization of energy storage and conversion systems.